If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -72 = 12x Solving -72 = 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. -72 + -12x = 12x + -12x Combine like terms: 12x + -12x = 0 -72 + -12x = 0 Add '72' to each side of the equation. -72 + 72 + -12x = 0 + 72 Combine like terms: -72 + 72 = 0 0 + -12x = 0 + 72 -12x = 0 + 72 Combine like terms: 0 + 72 = 72 -12x = 72 Divide each side by '-12'. x = -6 Simplifying x = -6
| 0.5x-2.1y=5.7 | | 300=25/x | | 6x+3=-8+3x+23 | | P=2l+2wforp | | (-4)p+(-3)(1-p)=3p+(-5)(1-p) | | 6x+10=4y | | e*x+3=21 | | S=4x^2-16x+88 | | x+7-4(x-1)=-10 | | x^2+7-10=0 | | 3y-4.6=20 | | 2x^4+11x-63=0 | | y=150*1.0894 | | -5(9+6x)=315 | | 40+3n=-23 | | f(x)=x^2-2+8 | | 72x+y=90 | | 5x+10=-22 | | 5(5x^2-6x+8)=0 | | 5x-8=2y+5 | | -2(-4x+6)=20 | | C=4c-6 | | 4(5-2n)-3n=4n-85 | | 4x(-7)=(-27) | | 0=5*cos(x) | | (-2x)+5=(-9) | | 8x+112=42 | | 11.4=8y | | (-11)=8x+13 | | 0=5*cosx | | 50/6-1/4=3/8 | | Y^2+4y+4-9y^2=0 |